Dobsinaite, Ca2Ca(AsO4)2·2H2O, a new member of the roselite group from Dobsina (Slovak Republic) - Sejkora,J.; Stevko,M.; Skoda,R.; Viskova,E.; Toman,J.; Hreus,S.; Plasil,J.; Dolnicek,Z. (Journal of Geosciences, 2021)
Dobsinaite, ideally Ca2Ca(AsO4)2·2H2O, is a new supergene mineral from the Dobsina deposit, Slovak Republic, associated with phaunouxite, picropharmacolite, erythrite-hörnesite, gypsum and aragonite. It forms white to pink clusters or polycrystalline aggregates up to 1-4 mm in size consisting of densely intergrown, slightly rounded thin tabular to platy crystals up to 0.1 mm in size. Dobsinaite has a white streak, vitreous luster, does not fluoresce under either short- or long-wave ultraviolet light. Cleavage on {010} is good, the Mohs hardness is ˜3, and dobsinaite is brittle with an uneven fracture. The calculated density is 3.395 g/cm3. Dobsinaite is optically biaxial negative, the indices of refraction are α´ = 1.601(2) and γ´ = 1.629(2) and 2Vmeas. is 60° (+/- 20°). Dobsinaite is monoclinic, space group P21/c, a = 5.990(2), b = 13.013(4), c = 5.726(2) Å, β = 108.47(3)°, V = 423.3(3) Å3, Z = 2. The seven strongest lines in the X-ray powder diffraction pattern are as follows: d (Å)/I(hkl): 5.197/37(110); 3.443/38(130); 3.385/66(031); 3.249/77(040); 3.201/42(13-1); 3.026/100(121) and 2.822/60(10-2). The chemical analyses by electron microprobe yielded (in wt. %) CaO 36.74, MgO 0.89, NiO 0.37, CoO 0.51, P2O5 0.03, As2O5 52.75, SO3 0.18, H2Ocalc. 8.31, total 99.78. The resulting empirical formula on the basis of 10 O atoms per formula unit is Ca2(Ca0.84Mg0.10Co0.03Ni0.02)Σ0.99[(AsO4)1.99(SO4)0.01]Σ2.00·2H2O. Dobsinaite is the Ca-dominant member of the roselite group as confirmed by stoichiometry, X-ray powder diffraction data and Raman spectroscopy. It is named after its type locality Dobsina, Slovak Republic. Dobsinaite was formed during weathering of primary Co and As-bearing ore minerals (safflorite, arsenopyrite) in a Ca enriched environment under relatively dry conditions.
Keywords: dobsinaite; calcium arsenate; new mineral; roselite group; Dobsina; Slovak Republic